Analisis Pengaruh Current Ratio, Price To Book Value Dan Earning Per Share Terhadap Harga Saham Dengan Price Earning Ratio Sebagai Variabel Moderasi - Franki Sinaga; Sri Yuni; Agus Kubertein; Mutmainah Mutmainah; Tatik Zulaika; Darmae Nasir (Jurnal Riset Ekonomi dan Akuntansi, 2023)
This study aims to determine the effect of the current ratio, price to book value, and earnings per share on stock prices in consumer goods manufacturing companies listed on the Indonesia Stock Exchange. This study uses a type of quantitative research. The data used in this research is secondary data with a period of 3 years. The method used in this study is Multiple Regression Analysis. As the dependent variable in this study the current ratio, price to book value, earnings per share, and stock prices as independent variables, as well as price earning ratio as a moderating variable. The results of this study are that partially price to book value and earnings per share have a positive and significant effect on stock prices, and the current ratio has a negative and insignificant effect on stock prices. And in moderation the price earning ratio as a moderating variable is able to strengthen the relationship between price to book value to stock prices, and the price earning ratio weakens the relationship between current ratio, earnings per share to stock prices. Simultaneously, the current ratio, price to book value and earnings per share together have a positive and significant effect on the stock price variable.